2019
DOI: 10.1101/871632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Euler Characteristic and Topological Phase Transitions in Complex Systems

Abstract: In this work, we use methods and concepts of applied algebraic topology to comprehensively explore topological phase transitions in complex systems. Topological phase transitions are characterized by the zeros of the Euler characteristic (EC) or by singularities of the Euler entropy and also indicate signal changes in the mean node curvature of networks. Here, we provide strong evidence that the zeros of the Euler characteristic can be interpreted as a complex network's intrinsic fingerprint. We theoretically … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…[41] In these cases, as is seen herein for the ferroelectric domain structures, the result is that not only does the phase fraction of the secondary phase change, but also how that phase is arranged within the primary phase. In turn, taking lessons from these other fields of study, we have applied analysis approaches developed therein [42][43][44] to the domain structures observed herein. In particular, we translate ideas of topology (a branch of mathematics that offers a means to characterize the shape of data objects) [44] including the so-called Euler characteristic (EC) which is a topologically invariant number that describes a topological space's shape or structure regardless of the way it is bent or stretch without breaking, [45] to explore these domain structures.…”
Section: Resultsmentioning
confidence: 99%
“…[41] In these cases, as is seen herein for the ferroelectric domain structures, the result is that not only does the phase fraction of the secondary phase change, but also how that phase is arranged within the primary phase. In turn, taking lessons from these other fields of study, we have applied analysis approaches developed therein [42][43][44] to the domain structures observed herein. In particular, we translate ideas of topology (a branch of mathematics that offers a means to characterize the shape of data objects) [44] including the so-called Euler characteristic (EC) which is a topologically invariant number that describes a topological space's shape or structure regardless of the way it is bent or stretch without breaking, [45] to explore these domain structures.…”
Section: Resultsmentioning
confidence: 99%
“…topological phase transitions in complex networks (Amorim et al 2019;Santos et al 2019) can also be identified between the changes in the dimensionality of the birth/death graphs mentioned above (Fig. 3e).…”
Section: Persistent Homologymentioning
confidence: 81%
“…This strategy has already been applied for investigating group differences between controls and glioma brain networks (Santos et al 2019) and typically developing children and children with attentiondeficit/hyperactivity disorder (Gracia-Tabuenca et al 2020). In other fields, topological phase transitions were also investigated in the S. cerevisiae and C. elegans protein interaction networks, reionisation processes, and evolving coauthorship networks (Amorim et al 2019;Giri and Mellema 2021;Lee et al 2021).…”
Section: Topological Phase Transitionsmentioning
confidence: 99%
“…This strategy has already been applied for investigating group differences between controls and glioma brain networks [64], and typically developing children and children with attention-deficit/hyperactivity disorder [26]. In other fields, topological phase transitions were also investigated in the S. cerevisiae and C. elegans protein interaction networks, reionization processes, and evolving coauthorship networks [70][71][72].…”
Section: Topological Phase Transitionsmentioning
confidence: 99%
“…Here we used the Gudhi package for the implementation of those steps [83]. The topological phase transitions in complex networks [64,70], which can also be identified between the changes in the dimensionality of the birth/death graphs mentioned above ( Fig 3E).…”
Section: Persistent Homologymentioning
confidence: 99%